Testosterone, prolactin, and oncogenic regulation of the prostate gland. A new concept: Testosterone-independent malignancy is the development of prolactin-dependent malignancy! - Leslie C. Costello; Renty B. Franklin (Frontiers Media S.A., 2018)
Hormone-independent malignancy is a major issue of morbidity and deaths that confronts prostate cancer. Despite decades of research, the oncogenic and hormonal implications in the development and progression of prostate malignancy remain mostly speculative. This is largely due to the absence and/or lack of consideration by contemporary clinicians and biomedical investigators regarding the established implications of the co-regulation of testosterone and prolactin in the development, maintenance, metabolism and functions of the prostate gland. Especially relevant is the major metabolic function of production of high levels of citrate by the peripheral zone acinar epithelial cells. Citrate production, along with growth and proliferation by these cells, is regulated by co-existing testosterone and prolactin signaling pathways; and by the oncogenic down-regulation of ZIP1 transporter/zinc/citrate in the development of malignancy. These relationships had not been considered in the issues of hormone-dependent malignancy. This review provides the relevant background that has established the dual role of testosterone and prolactin regulation of the prostate gland; which is essential to address the implications in the oncogenic development and progression of hormone-dependent malignancy. The oncogenic factor along with testosterone-dependent and prolactin-dependent relationships leads to the plausible concept that androgen ablation for the treatment of testosterone-dependent malignancy results in the development of prolactin-dependent malignancy; which is testosterone-independent malignancy. Consequently, both testosterone ablation and prolactin ablation are required to prevent and/or abort terminal hormonedependent prostate cancer.